1989
DOI: 10.1002/j.1460-2075.1989.tb08399.x
|View full text |Cite
|
Sign up to set email alerts
|

A collagen-binding 59-kd protein (fibromodulin) is structurally related to the small interstitial proteoglycans PG-S1 and PG-S2 (decorin).

Abstract: We have determined the primary structure of a 59 kd collagen binding protein which is present in many types of connective tissues, e.g. cartilage, tendon, skin, sclera and cornea. The amino acid sequence, deducted from a 2662 bp cDNA clone, predicts a 42 kd protein with a high content of leucine residues. Most of the protein consists of homologous 23 amino acid residues repeats with predominantly leucine residues in conserved positions. Similar leucine rich repeats have been identified in a number of proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
187
0
10

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(202 citation statements)
references
References 28 publications
5
187
0
10
Order By: Relevance
“…The size of the avian TSP-4 transcript is in agreement with the sizes of amphibian (3.3 kb) and human (3.4 kb) TSP-4 mRNAs reported previously . It is similar in size to TSP-3 mRNA (3.5 kb in mouse, Vos et al, 1992; 3.4 kb in human, Lawler et al, 1993a), and is significantly larger than bovine COMP mRNA (2.5 kb, Oldberg et al, 1992). In addition, cTSP-4 hybridized to a 3.4 kb mRNA present in adult human heart and skeletal muscle (data not shown).…”
Section: Southern and Northern Blot Analysismentioning
confidence: 80%
See 1 more Smart Citation
“…The size of the avian TSP-4 transcript is in agreement with the sizes of amphibian (3.3 kb) and human (3.4 kb) TSP-4 mRNAs reported previously . It is similar in size to TSP-3 mRNA (3.5 kb in mouse, Vos et al, 1992; 3.4 kb in human, Lawler et al, 1993a), and is significantly larger than bovine COMP mRNA (2.5 kb, Oldberg et al, 1992). In addition, cTSP-4 hybridized to a 3.4 kb mRNA present in adult human heart and skeletal muscle (data not shown).…”
Section: Southern and Northern Blot Analysismentioning
confidence: 80%
“…The other four family members have been designated thrombospondin-2 (TSP-2; Bornstein et al, 1991;LaBell et al, 1992), thrombospondin-3 (TSP-3; Vos et al, 1992), thrombospondin-4 (TSP-4; Lawler et al, 1993a), and cartilage oligomeric matrix protein (COMP; Oldberg et al, 1992: see reviews by Bornstein, 1992;Adams and Lawler, 1993a). On the basis of their primary structures, the thrombospondins can be divided into two subgroups (Lawler et al, 199313;Adams and Lawler, 1993a).…”
Section: Introductionmentioning
confidence: 99%
“…Fibromodulin is exclusively glycosylated by short chains of keratan sulphate (KS) [13][14][15][16]. In addition, Plaas et al [17] have demonstrated that, in 3-month-old bovine articular cartilage, only four out of the five potential glycosylation sites were substituted by either KS or an N-linked oligosaccharide.…”
Section: Introductionmentioning
confidence: 99%
“…CHAD is also expressed in other tissues that experience load, such as bone and tendon, albeit in a lower abundance (9 -11). Thus, CHAD shows a very restricted distribution especially when compared with other leucine-rich repeat proteins (12)(13)(14).…”
mentioning
confidence: 99%